1994
DOI: 10.1073/pnas.91.2.514
|View full text |Cite
|
Sign up to set email alerts
|

Somatic diversification in the heavy chain variable region genes expressed by human autoantibodies bearing a lupus-associated nephritogenic anti-DNA idiotype.

Abstract: Monoclonal anti-DNA antibodies bearing a lupus nephritis-associated idiotype were derived from five patients with systemic lupus erythematosus (SLE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…In the heavy chain variable regions, mutations in CDR2 are more prevalent than mutations in CDR1. This is consistent with other studies showing an increased frequency of somatic mutation in CDR2 of V H 3 and V H 4 genes encoding autoantibodies (18,38). Radic and Weigert have suggested that CDR2 of the heavy chain plays an important role in DNA binding, and a large number of murine anti-DNA antibodies also display extensive mutation of CDR2 in the heavy chain V region (39).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the heavy chain variable regions, mutations in CDR2 are more prevalent than mutations in CDR1. This is consistent with other studies showing an increased frequency of somatic mutation in CDR2 of V H 3 and V H 4 genes encoding autoantibodies (18,38). Radic and Weigert have suggested that CDR2 of the heavy chain plays an important role in DNA binding, and a large number of murine anti-DNA antibodies also display extensive mutation of CDR2 in the heavy chain V region (39).…”
Section: Discussionsupporting
confidence: 81%
“…Since nephritogenic antibodies are often cationic (16)(17)(18), it was of interest to determine the isoelectric points of the heavy and light chain variable region sequences. Most F4 reactive heavy chains are cationic; only two are not, and these two derive from non-DNA-binding antibodies (Table IV).…”
Section: Resultsmentioning
confidence: 99%
“…The V H germlines DP33(V H 3), V H 4.18, DP53(V H 43) and V H 44.21 used by MCLs examined in the present study are frequently employed by autoantibodies such as rheumatoid factors and natural autoantibodies (Demaison et al, 1994;Huang & Stollar, 1993;Ermel et al, 1993). Thus, MCL may also be transformed from autoreactive B-cell clones.…”
Section: Discussionmentioning
confidence: 97%
“…The presence or absence of the 4-61 segment also could affect the relative location of 4-51. On the other hand, these two segments were shown to be involved in generating anti-DNA autoantibodies in the patients with systemic lupus erythematosus (42)(43)(44). The usage of the V H segments could be considerably affected by their organization.…”
Section: Discussionmentioning
confidence: 99%